Logic and Argumentation: 4th International Conference, CLAR 2021, Hangzhou, China, October 20-22, 2021, Proceedings - Baroni, Pietro; Benzmüller, Christoph; Wáng, Yὶ N (Lecture Notes in Computer Science, 2021)
This book constitutes the refereed proceedings of the 4th International Conference on Logic and Argumentation, CLAR 2021, held in Hangzhou, China, in October 2021. The 20 full and 10 short papers presented  together with 5 invited papers were carefully reviewed and selected from 58 submissions. The topics of accepted papers cover the focus of the CLAR series, including formal models of argumentation, a variety of logic formalisms, nonmonotonic reasoning, dispute and dialogue systems, formal treatment of preference and support, and well as applications in areas like vaccine information and processing of legal texts.